Electrochemical Behavior of Ti6Al4V Alloy Used in Dental Implants Immersed in Streptococcus gordonii and Fusobacterium nucleatum Solutions - De la Garza Ramos, Myriam Angélica; Estupiñan López, Francisco Humberto; Gaona Tiburcio, Citlalli; Beltrán Novelo, Lucía G.; Zambrano Robledo, Patricia del Carmen; Cabral Miramontes, José Ángel; Almeraya Calderón, Facundo (Molecular Diversity Preservation International, 2020)
The titanium alloy, Ti6Al4V, is used in dentistry for dental implants because of its excellent resistance to corrosion and its high biocompatibility. However, periimplantitis is considered the main reason for treatment failure. The Ti6Al4V alloy was used to study the corrosion behavior for dental implant applications, using an experimental arrangement of three electrodes with the bacteria Streptococcus gordonii and Fusobacterium nucleatum, in addition to Ringer’s lactate as electrolytes, at 37 °C and a pH of 5.6. Their electrochemical behavior was studied by open circuit potential (OCP) and cyclic potentiodynamic polarization (CPP) according to ASTM G3-14 and ASTM G61-11, respectively. Scanning electron microscopy (SEM) was employed to determine the morphology of the alloy studied. An experimental model, in situ, was established with the bacteria present in an oral environment to understand the electrochemical behavior of the alloy used in dental implants. The greatest corrosion in Ti6Al4V alloy was produced by the medium that contained the bacterium Streptococcus gordonii, which is considered a primary colonizer. In addition, the Ti6Al4V alloy presented uniform corrosion in the three solutions at the different exposure times showing a negative hysteresis in CPP.